Oxaliplatin plus S-1 or capecitabine as neoadjuvant or adjuvant chemotherapy for locally advanced gastric cancer with D2 lymphadenectomy: 5-year follow-up results of a phase II−III randomized trial - Xue, Kan (AME Publishing Company, 2018)

(untitled) (Chin J Cancer Res)
OBJECTIVE: To compare the effect of neoadjuvant chemotherapy (NACT) with adjuvant chemotherapy (ACT) using oxaliplatin plus S-1 (SOX) or capecitabine (CapeOX) on gastric cancer patients with D2 lymphadenectomy. METHODS: This was a two-by-two factorial randomized phase II−III trial, and registered on ISRCTN registry (No. ISRCTN12206108). Locally advanced gastric cancer patients were randomized to neoadjuvant SOX, neoadjuvant CapeOX, adjuvant SOX, or adjuvant CapeOX arms. Primary analysis was performed on an intention-to-treat (ITT) basis using overall survival (OS) as primary endpoint. RESULTS: This trial started in September 2011 and closed in December 2012 with 100 patients enrolled. Treatment completion rate was 56%, 52%, 38% and 30% in the four arms, respectively. NACT group had fewer dropouts due to unacceptable toxicity (P=0.042). Surgical complication rate did not differ by the four groups (P=0.986). No survival significant difference was found comparing NACT with ACT (P=0.664; 5-year-OS: 70% vs. 74% respectively), nor between the SOX and CapeOX groups (P=0.252; 5-year-OS: 78% vs. 66% respectively). Subgroup analysis showed SOX significantly improved survival in patients with diffuse type (P=0.048). CONCLUSIONS: No significant survival difference was found between NACT and ACT. SOX and CapeOX had good safety and efficacy as neoadjuvant regimens. Diffuse type patients may survive longer due to SOX.